Discovery of 1a, 2, 5, 5a-tetrahydro-1H-2, 3-diaza-cyclopropa[a]pentalen-4-carboxamides as potent and selective CB2 receptor agonists. Issue 2 (15th January 2015) - Han, Sangdon; Thoresen, Lars; Zhu, Xiuwen; Narayanan, Sanju; Jung, Jae-Kyu; Strah-Pleynet, Sonja; Decaire, Marc; Choi, Karoline; Xiong, Yifeng; Yue, Dawei; Semple, Graeme; Thatte, Jayant; et al.
Graphical abstract: Abstract: The design and synthesis of novel 1 a, 2, 5, 5 a -tetrahydro-1 H -2, 3-diaza-cyclopropa[ a ]pentalen-4-carboxamide CB2 selective ligands for the potential treatment of pain is described. Compound ( R, R )-25 has good balance between CB2 agonist potency and selectivity over CB1, and possesses overall favorable pharmaceutical properties. It also demonstrated robust in vivo efficacy mediated via CB2 activation in the rodent models of inflammatory and osteoarthritis pain after oral administration.